Acquired Dyslexia and Dysgraphia in Chinese - Wengang Yin; Shengxi He; Brendan Stuart Weekes (Behavioural Neurology)
Understanding how the mappings between orthography and phonology in alphabetic languages are learned, represented and processed has been enhanced by the cognitive neuropsychological investigation of patients with acquired reading and writing disorders. During the past decade, this methodology has been extended to understanding reading and writing in Chinese leading to new insights about language processing, dyslexia and dysgraphia. The aim of this paper is to review reports of patients who have acquired dyslexia and acquired dysgraphia in Chinese and describe the functional architecture of the reading and writing system. Our conclusion is that the unique features of Chinese script will determine the symptoms of acquired dyslexia and dysgraphia in Chinese.